The Effect of PAD, DAU, DAK, BHSDA, Investment, and Economic Growth on Poverty in North Maluku Province - Hatim, Fajri; Hijrasil, Hijrasil (International Journal of Social Science and Business, 2024)
This study examines the relationship between various economic factors—regional own-source revenue (PAD), general allocation funds (DAU), special allocation funds (DAK), natural resource revenue sharing (BHSDA), investment, and economic growth (PDRB)—and poverty levels in North Maluku Province. While economic growth is commonly associated with improvements in community welfare, North Maluku presents a paradox: despite increasing economic growth, poverty rates have also risen. The objective of this research is to assess the impact of these factors on poverty alleviation in the region. Using variance decomposition analysis, the study finds that the variables of PAD, DAU, DAK, BHSDA, investment, and PDRB collectively have a minimal influence on poverty reduction in North Maluku. This suggests that other factors, not captured by these variables, may play a more significant role in shaping poverty outcomes. The findings highlight the complexity of poverty dynamics in the region and imply that additional policy measures beyond economic growth and fiscal transfers may be necessary to effectively reduce poverty in North Maluku.